The importance of human relationships, ethics and recovery-orientated values in the delivery of CBT for people with psychosis. Issue 2 (3rd April 2017) - Brabban, Alison; Byrne, Rory; Longden, Eleanor; Morrison, Anthony P.
Abstract: Cognitive behavioural therapy for psychosis (CBTp) is, at times, perceived as a technical therapy that undervalues the importance of human relationships and the fundamental principles on which CBTp itself is based (such as collaboration, validation, optimism and recovery-orientated practice). As such, it can be dismissed by service users or practitioners as undesirable. It is also possible that delivering CBTp that does not adhere to these values can be unhelpful or harmful. We review the evidence regarding what service users want from mental health services and the ability of CBTp to meet these standards. Evidence from qualitative studies and randomised controlled trials suggests that CBTp should be delivered in a manner that is both acceptable to, and empowering of, service users. We suggest strategies that are likely to maximise the likelihood of successful implementation that is consistent with both values base and evidence base.